Општество на знаење или како Болоња ја (из)брка етиката - Donev, Dejan (Аз-Буки, Скопје (Филозофско друштво на Македонија), 2010)
The Bologna declaration, like nothing else so far, especially in countries which aspire to become members in community that brought up the Declaration, transformed in absolute text that usually somewhere is equalized with the Bible of new believes - Society of Knowledge. The whole human history shows that every uncritical bowing at the end brings us to the denial on which kept us in our development - an ethics founded on responsibility for what imposes like a final aim in one process.
Society of Knowledge, or How Bologna Chased Away Etihcs
Keywords: society of knowledge, ethics, responsibility, development